The Effect of Compensation and Motivation on Employee Turnover at PT Indofood CBP Sukses Makmur Tbk. Snack Division - Astuti, Widia (East Asian Journal of Multidisciplinary Research, 2024)
This study examined the impact of salary and motivation on employee turnover in the Snack Division of PT Indofood CBP Sukses Makmur Tbk., using a quantitative causal design with a census sample of 120 employees. The results revealed that salary and motivation significantly and positively affect turnover, as shown by t-test values (t_count = 9.134 for salary, t_count = 4.024 for motivation) and a significance level of 0.000 (< 0.1). Additionally, the combined effect of salary and motivation on turnover was significant, with F_count = 43.333 surpassing F_table = 3.07. The findings highlight the critical role of compensation and motivation in influencing turnover.